Tailoring treatment of nonsmall cell lung cancer by tissue type: role of pemetrexed - Powell, Steven F (Dove Medical Press, 2009)
Pemetrexed (ALIMTA, LY231514, MTA) is a novel multitargeted antifolate that is currently approved for the treatment of metastatic nonsmall cell lung cancer (NSCLC). Recent evidence reveals that the drug’s efficacy is limited to nonsquamous lung cancer histology. As we further understand the drug’s mechanisms of action, new genomic and proteomic evidence is shedding light on why some patients respond while others do not. The first goal of this review is to briefly review pemetrexed’s mechanism of action, resistance patterns, toxicity profile, and pharmacokinetics. We will also review the clinical trials that led to its use in NSCLC, with special attention to data showing that pemetrexed has greater efficacy in nonsquamous histologies of NSCLC. Furthermore, we will discuss the hypotheses for the genomic and proteomic basis for this variation in efficacy. Finally, we will report the future directions for pemetrexed as a personalized agent for nonsquamous NSCLC.